Detection of Mycoplasma bovirhinis and bovine coronavirus in an outbreak of bovine respiratory disease in nursing beef calves - McDaneld, Tara G.; Workman, Aspen M.; Chitko-McKown, Carol G.; Kuehn, Larry A.; Dickey, Aaron; Bennett, Gary L. (Frontiers in Microbiomes, 2022)
Respiratory disease incidence is intimately associated with an animal’s commensal bacteria populations (microbiome), as microbes that are involved with morbidity and mortality are commonly found in animals with no sign of disease. In addition, viral pathogens affect the immune system and appear to play an integral role in the overall incidence of bovine respiratory disease (BRD); so, an understanding of the interaction of bacterial and viral pathogens in the upper respiratory tract (URT) may help to understand the impact of these pathogens on development of BRD. For this research, the goal was to characterize bacterial and viral populations in the URT of nursing beef calves at initial vaccination and at the time of a BRD outbreak. Nasal swabs were collected at initial vaccination (average 45 days of age) and again at the time of the BRD outbreak (average 126 days of age). DNA and RNA were extracted from nasal swabs to evaluate bacterial and viral populations in the URT. Whole blood was also collected at the time of the outbreak for determination of complete blood counts. To evaluate the microbiome, the 16S ribosomal RNA (rRNA) gene was amplified by PCR and sequenced using next-generation sequencing (Illumina MiSeq). To evaluate the viral pathogens, multiplex reverse transcription real-time polymerase chain reaction and next-generation sequencing (Illumina NextSeq) was completed. Overall, evaluation of these samples revealed that at the time of the outbreak, all calves were nasally shedding bovine coronavirus and a large percentage had a coinfection with Mycoplasma sp., with Mycoplasma bovirhinis being the predominant species. Neither bovine coronavirus nor Mycoplasma sp. were present at high abundance at the earlier timepoint of initial vaccination. When comparing bacterial population diversity between the two sampling timepoints, alpha diversity was significantly greater at initial vaccination compared to the outbreak (P-value <0.001). Values of leukocytes at the time of the outbreak were also identified to be significantly different between calves with normal or elevated rectal temperatures (P-value <0.05). Analysis of the respiratory microflora in the URT during initial vaccination and the outbreak will provide insight into the distribution of bacterial and viral populations in nursing beef calves.